Pendekatan Pembelajaran Anak Usia Dini pada Kurikulum Merdeka: Membangun Kemandirian dan Kreativitas di TKS Muslimat NU XVIII Taro'an Pamekasan - Nurul Hidayati Nurul; Shohebul Hajad (ABATATSA: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The Merdeka Curriculum offers a new approach to early childhood education (PAUD), which emphasizes developing children's independence and creativity. This research aims to analyze the implementation of the learning approach in the Merdeka Curriculum at the Muslimat NU XVIII Taro'an Pamekasan Kindergarten, with a focus on how this strategy helps build children's independence and creativity. The research method used is a qualitative approach using observation, interviews and document analysis. The research results show that the implementation of the Merdeka Curriculum in the Muslimat NU XVIII Kindergarten has succeeded in encouraging children to be more independent and creative through interactive and participatory learning activities. However, there are challenges in implementation, such as gaps in understanding among teachers and limited resources. Therefore, it is necessary to strengthen teacher training and increase resources as an effort to optimize the implementation of the Independent Curriculum.